Controlled macroscopic shape evolution of self-growing polymeric materials - Xinhong Xiong; Xiaozhuang Zhou; Haohui Zhang; Michael Aizenberg; Yuxing Yao; Yuhang Hu; Joanna Aizenberg; Jiaxi Cui (Nature Communications)
Abstract Living organisms absorb external nutrients to grow, changing their macroscopic shapes to meet various challenges through mass transport and integration. While several strategies have been developed to create dynamic polymers that allow for mainchain remodelings to mimic the growing ability of living organisms, most are limited to simple homogeneous growth without complex control of global geometric transformation during growth. Herein, we report an approach to design controlled, growth-induced shape transformation in synthetic materials, in which significant mass transport within the materials is induced by spatially controlled polymerization leading to reshaping the materials. This method is demonstrated using silicone systems made through anionic ring-opening polymerization (anionic ROP) of octamethylcyclotetrasiloxane (D4) with a strong base as the catalyst. We show that a flat square sample can be transformed into a sphere through growth without the need for remolding and preprogramming. By varying the composition of the monomer mixture provided to the samples, and the modes of triggering and shutting down polymerization, we achieve exquisite control over growing polymeric objects into various sizes and shapes, modulating their mechanical properties, self-healing ability, and availability of active sites for further growth from a desired location. We envision this strategy opening an innovative direction in preparing soft materials with specific shapes or surface morphologies.